PENGGUNAAN ENZIM KASAR SELULASE Trichoderma reesei FNCC 6012 UNTUK PRODUKSI BIOETANOL DARI AMPAS TEBU OLEH Saccharomyces cerevisiae FNCC 3012 - , PUSPANINDYA YUDAPUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bioethanol production by SSF (Simultaneous Saccharification and Fermentation) was studied using cellulose crude enzymes of Trichoderma reesei FNCC 6012 for bagasse fermentation by Saccharomyces cerevisiae FNCC 3012. T. reesei FNCC 6012 were incubated at straw for crude enzymes production at different temperatures (27 ° C and 37 ° C) and different incubation times (7 and 9 days) for cellulose crude enzymes. The crude enzymes obtained by filtrating the incubated straws. Filtrate then used in SSF and ethanol production from bagasse by S. cereviceae. A commercial cellulose enzyme (ESK) was used as a standard. The highest cellulolytic activity was shown in crude enzyme treatment pre-incubated at 37 °C for 9 days, was 0.258 IU/mL. While, the highest reducing sugar concentration and ethanol productivity was shown in crude enzyme treatment preincubated for at 27 °C 9 days, was 1575,3 mg/ml filtrate for reducing sugar concentration and 0.590% for ethanol concentration. From those results, it can be concluded that crude enzyme of T. reesei FNCC 6012 can be used for ethanol production although the ethanol produced by this method has low concentration.